Improving Diagnostic and Treatment Precision for Negative Symptoms of Schizophrenia using Quantitative Electroencephalography and Transcranial Direct Current Stimulation: A Case Report - Deepan Raj; Srinivas Rajkumar; Priya Sivashankar (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Schizophrenia is a major mental illness associated with significant disability. Negative symptoms represent a key determinant of longterm morbidity and poor functional outcomes. This is a case report of a 22-year-old male presenting with poor functional recovery despite apparent resolution of psychotic symptoms (hallucinations and delusions) on antipsychotics. In follow-up his antipsychotic dose was up titrated along addition of anti-depressants with suspicion of primary negative vs depressive symptoms. He did not show any improvement in his negative symptoms such as avolition, anhedonia, apathy, alogia, asociality. Comprehensive reassessment, including clinical evaluation and Quantitative Electroencephalography (qEEG), showed findings such as frontal dysfunction and raised the possibility of secondary negative symptoms related to antipsychotic treatment rather than a primary deficit state. Based on this, pharmacotherapy was optimised by switching from high-dose risperidone to amisulpride and augmenting with transcranial Direct Current Stimulation (tDCS) targeting the left dorsolateral prefrontal cortex. Significant improvement was observed in affect, speech output, social interaction, and Cognitive Performance (CPT), supported by normalisation of electrophysiological markers. This case highlights the importance of distinguishing primary and secondary negative symptoms and suggests a potential role for qEEG in guiding pharmacological and other interventions. This case study challenges the conventional wisdom that uptitrating antipsychotics in incomplete remission of psychotic illness can be counterproductive leading to secondary negative symptoms. In such cases adequacy of dopamine blockade can be assessed by qEEG.